2018
DOI: 10.1002/ppul.24183
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high‐mobility group box 1 and caspase in bronchiolitis

Abstract: Objective Nasal biomarkers have potential to add objectivity to the clinical assessment of the child with bronchiolitis. We aim to study, if nasal caspase and high‐mobility group box 1 protein (HMGB1) levels differ between patients who were hospitalized and those discharged from the emergency department (ED), among patients with bronchiolitis. Methods Using an observational cross‐sectional study design, we recruited patients younger than 24 months presenting to the ED from September 1, 2015 to May 31, 2017 wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…It is important to know whether it is the initial epithelial injury that is responsible for severity and sequelae, or whether the inflammatory response to the viral agent predisposes the patient to relapses. Much effort has been made to identify novel biological markers measurable during the course of acute bronchiolitis for clinically effective prediction of disease severity and later wheezing . Our team has studied epithelial injury biomarkers in acute bronchiolitis, but found no correlation between serum levels of KL‐6 2 , or serum‐soluble receptor for advanced glycation end‐product, and severity of acute bronchiolitis and risk of wheezing bronchitis.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to know whether it is the initial epithelial injury that is responsible for severity and sequelae, or whether the inflammatory response to the viral agent predisposes the patient to relapses. Much effort has been made to identify novel biological markers measurable during the course of acute bronchiolitis for clinically effective prediction of disease severity and later wheezing . Our team has studied epithelial injury biomarkers in acute bronchiolitis, but found no correlation between serum levels of KL‐6 2 , or serum‐soluble receptor for advanced glycation end‐product, and severity of acute bronchiolitis and risk of wheezing bronchitis.…”
Section: Introductionmentioning
confidence: 99%
“…Chong et al [24] reported that the mRIS, a modified version of the Tal score (albeit different from the modified Tal score [mTal]) had a fair ability at discriminating between those who required non-invasive respiratory support, but a poor ability at discriminating by admission, intravenous hydration and LOS≥ 2 days. Another publication [25] using a subset of the same dataset similarly reported a poor ability of the mRIS at discriminating by admission.…”
Section: Discriminative Validitymentioning
confidence: 91%
“…In addition to clinical studies, HMGB1 levels in bronchoalveolar lavage fluid and lung tissue were significantly increased in animal models of pneumonia induced by adenovirus infection, and the expression of the receptors TLR4/9 and RAGE also varied with the changes in HMGB1, confirming that the HMGB1 signaling pathway plays a role in the occurrence and development of adenovirus‐mediated pneumonia 80 . The level of HMGB1 in the nasal secretions of children with bronchiolitis requiring hospitalization was significantly higher than those of children who were allowed to leave the hospital after emergency treatment, which makes it possible to grade the severity of acute bronchiolitis in children by measuring HMGB1 in nasal secretions 81 . Furthermore, HMGB1 was significantly increased in the serum of children with severe pneumonia who were infected with H1N1 influenza virus and was significantly associated with the upregulation of 10 other cytokines 80 .…”
Section: Role Of Hmgb1 In Pediatric Diseasesmentioning
confidence: 99%